2016
DOI: 10.3389/fmats.2016.00019
|View full text |Cite
|
Sign up to set email alerts
|

Finding New Perovskite Halides via Machine Learning

Abstract: Advanced materials with improved properties have the potential to fuel future technological advancements. However, identification and discovery of these optimal materials for a specific application is a non-trivial task, because of the vastness of the chemical search space with enormous compositional and configurational degrees of freedom. Materials informatics provides an efficient approach toward rational design of new materials, via learning from known data to make decisions on new and previously unexplored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(105 citation statements)
references
References 36 publications
1
104
0
Order By: Relevance
“…Approximately 220 ABX 3 halide perovskites were found to the Goldschmidt tolerance factor of 0.98–1.00. Furthermore, another investigation has shown that a certain data set of ABX 3 halide perovskites with high formability has the octahedral factor, the ratio of r B to r A , between approximately 0.45 and 0.70 . Therefore, in addition to a narrow Goldshcmidt Tolerance factor ranging from 0.98 to 1.00 for the high probability of being cubic, the perovskites were filtered using the octahedral factor of 0.45–0.70.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 220 ABX 3 halide perovskites were found to the Goldschmidt tolerance factor of 0.98–1.00. Furthermore, another investigation has shown that a certain data set of ABX 3 halide perovskites with high formability has the octahedral factor, the ratio of r B to r A , between approximately 0.45 and 0.70 . Therefore, in addition to a narrow Goldshcmidt Tolerance factor ranging from 0.98 to 1.00 for the high probability of being cubic, the perovskites were filtered using the octahedral factor of 0.45–0.70.…”
Section: Resultsmentioning
confidence: 99%
“…Advanced quantum mechanical DFT modeling offers a great opportunity for the materials science community to characterize the electronic, structural, thermodynamic, and mechanical properties of thousands of materials, especially when combined with high‐throughput screening techniques ,,. As such, intensive investigations of the immense chemical spectrum are being increasingly pursued, which enables scientists to design and discover new photovoltaic materials with optimal properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To accelerate the design and realization of novel materials, a number of recent studies have screened promising candidates across a variety of categories, including light-emitting molecules, 1 perovskite compounds, [2][3][4][5] catalysts, 6,7 thermoelectrics, [8][9][10][11][12] and metal-organic frameworks. 13,14 Accordingly, the rise of virtual materials screening, along with high-throughput first-principles computations and experimentation, has resulted in the creation of numerous accessible databases for the materials science community.…”
Section: Introductionmentioning
confidence: 99%
“…We perform synthesis screening on SrTiO 3 and BaTiO 3 syntheses, since these materials systems have only hundreds of text-mining-accessible published syntheses, and thus provide an environment for examining the advantages of data volume augmentation. We also visually explore two-dimensional learned VAE latent vector spaces to investigate potential driving factors for brookite TiO 2 formation and to understand ion intercalation effects in MnO 2 phase selection.…”
Section: Introductionmentioning
confidence: 99%